(untitled) (International Journal of Physiotherapy, 2017)
Background: Cerebral palsy is a nonprogressive neuro-developmental disorders that are caused by damage to the developing brain and affect movement and posture. Children with cerebral palsy suffer difficulty in motor function (coordination and control).The present inquiry investigated the impact of conductive education on motor skills in children having cerebral palsy. Methods: A quasi-experimental research was done using pretest-posttest and control group design. The study subjects consisted of all children with cerebral palsy in Shiraz. A sample of 30 subjects was randomly chosen to employ convenience sampling procedure and classified to two groups of treatment (15 subjects) and control (15 subjects). The pretest was performed for both groups, and the experimental group received conductive education in 20 sessions. While the control subjects did not have this education, finally, the post-test was performed for both groups. The Lincoln-Oseretsky test was used to measure motor skills. The data were analyzed using ANCOVA and MANCOVA. Results: The results showed that conductive education had a significant effect on motor skills (P<0.001) and its subscales such as speed of movement (P<0.001), general static coordination (P<0.001), general dynamic coordination (P<0.001), dynamic manual coordination (P<0.001), synchronous-asymmetrical voluntary movements (P<0.001), and asynchronous-asymmetrical voluntary movements (P<0.001) in children with cerebral palsy. Conclusion: The findings indicated the effectiveness of conductive education on cerebral palsy children’s motor skills. Therefore, it is recommended to design and implement a conductive education program to improve motor skills of cerebral palsy children.